Aerial phytomass of four communities located in a topographic catena in the hilly region of La Pampa (Semiárida, 2020)
An area in the rolling country of La Pampa was chosen to determine standing crop and production of a natural grassland. Production was very distinct in the different communities growing in high and middle slope, low slope and bottomland. In the first area the summer desirable species were dominants in the second community were very abundant the winter good species. In the last community were very frequent the undesirable grasses.